The regional economic consequences of Less Favoured Area support in Poland: A regional general equilibrium analysis. - James Giesecke; Mark Horridge; Katarzyna Zawalinska (European Regional Science Association (ERSA), 2010)
The Common Agricultural Policy (CAP) is one of the most complex and also the most costly of all EU policies. It comprises over 40 financing streams, including Pillar I and Pillar II measures which are highly regulated. In the case of Poland, these are directed to all 16 NUTS2 regions. We are modelling here the regional and thus national consequences of the CAP's most costly Pillar II measure in Poland, so called Less Favoured Areas support (LFA). It is complex, when we recognise the multipurpose of this measure and significant amount of funds directed at a large number of regions. To handle the regional complexity of this problem, we require a multi-regional model. Such a model must be detailed in its disaggregation of industries, commodities and households if it is to be capable of reflecting the complexity of this measure. As such, we use a large-scale multi-regional CGE model. The model is tailored to reflect the complexity of the rural development policy (Pillar II), of which LFA is the largest part in Poland. Of the 82 region-specific sectors in the model, over 20 is related to agricultural production. The model distinguishes rural and urban households in each region and is based on the most recent IO tables of 2005. We propose a framework for mapping the individual financing stream of the LFA to the specific structural variables relating to specific type of land (LFA and nonLFA) in each region. As to our best knowledge such an approach was never conducted before with respect not only of LFA but also Pillar II measures in general.
Keywords: P50; C68; O18; 330; Comparative Economics; Computable General Equilibrium Models; Regional and Rural policy